STUDIES OF OPPORTUNITY RECOGNITION PROCESS: CHARACTERISTICS OF TUNISIAN ENTREPRENEUR PROFILE - Morched, Salim; Jarboui, Anis (APPS Publications, 2021)
Entrepreneurial research has largely raised the question of the resources and profile characteristics of the entrepreneur required throughout the entrepreneurial process: recognition of an entrepreneurial opportunity, creation, and development. Entrepreneurs often find it challenging to obtain the resources they need as soon as they are overwhelmed by the desire to recognize an opportunity to do business independently. On the one hand, our problem emanates from the scarcity of work on the specificities of entrepreneurs in Tunisia, in this case, those of private companies. On the other hand, any influences that their characteristics might have on their competence in identifying opportunity. Therefore, it would be a question of trying to identify the profile of the entrepreneur in Tunisian companies and appreciate the possible impacts that it could have on the characteristics theoretically considered within the upstream entrepreneurial process. In this perspective, we propose to focus our thinking, on the one hand, on the approach supported by entrepreneurs to recognize an entrepreneurial opportunity and, on the other hand, its impact on the recognition of entrepreneurial opportunity mobilized in this approach. This study explored the process of recognizing the opportunities of 80 Tunisian entrepreneurs, who were all recognized as having business opportunities and different characteristics.